Proteomic Profiling as a Diagnostic Biomarker for Discriminating Between Bipolar and Unipolar Depression - Kittel-Schneider, Sarah; Hahn, Tim; Haenisch, Frieder; McNeill, Rhiannon; Reif, Andreas; Bahn, Sabine (Frontiers in Psychiatry, 2020)
Introduction: Affective disorders are a major global burden, with approximately 15% of people worldwide suffering from some form of affective disorder. In patients experiencing their first depressive episode, in most cases it cannot be distinguished whether this is due to bipolar disorder (BD) or major depression (MDD). Valid fluid biomarkers able to discriminate between the two disorders in a clinical setting are not yet available. Material and methods: 70 depressed patients suffering from BD (bipolar I and II subtypes) and 42 patients with major depression (MDD) were recruited and blood samples were taken for proteomic analyses after 8h fasting. Proteomic profiles were analysed using the Multiplex Immunoassay platform from Myriad Rules Based Medicine (Myriad RBM; Austin, Texas, USA). Human DiscoveryMAPTM was used to measure the concentration of various proteins, peptides and small molecules. The total number of measured analytes differed between 190 and 257 in the four different batches. A multivariate predictive model was consequently constructed to differentiate between BD and MDD. Results: Based on the various proteomic profiles, the algorithm could discriminate depressed BD patients from unipolar depressed patients with an accuracy of 67%. Discussion: The results of this preliminary study suggest that future discrimination between bipolar and unipolar depression in a single case could be possible, using predictive biomarker models based on blood proteomic profiling.